2018
DOI: 10.5194/essd-2018-28
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DamaGIS: a multisource geodatabase for collection of flood-related damage data

Abstract: Abstract. The present paper introduces a new database for collection of flood-related damage and assessment at the local scale. Every year in France, recurring flood events result in several million Euros of damage, and reducing the heavy consequences of floods has become a high priority. However, actions to reduce the impact of floods are often hindered by the 10 lack of damage data on past flood events. Even if partial data were available, data sharing within the research community is very limited and closel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…floods, even in ungauged catchments (Payrastre et al, 2015(Payrastre et al, , 2016. A very recent database gathered flood-related damage data since 2011 in the south of France at a fine scale (Saint-Martin et al, 2018). Javelle et al (2014) demonstrated that these data provide valuable information for evaluating the simulated flood peak.…”
mentioning
confidence: 99%
“…floods, even in ungauged catchments (Payrastre et al, 2015(Payrastre et al, , 2016. A very recent database gathered flood-related damage data since 2011 in the south of France at a fine scale (Saint-Martin et al, 2018). Javelle et al (2014) demonstrated that these data provide valuable information for evaluating the simulated flood peak.…”
mentioning
confidence: 99%